Capacity of proton beams in preserving normal liver tissue during proton beam therapy for hepatocellular carcinoma. (3rd November 2020) - Tsai, Yu-Lun; Takei, Hideyuki; Iizumi, Takashi; Okumura, Toshiyuki; Sekino, Yuta; Numajiri, Haruko; Ishikawa, Hitoshi; Sakae, Takeji; Sakurai, Hideyuki
Abstract: Unirradiated liver volume (ULV) preservation rate is an important factor associated with radiation-induced liver disease (RILD) in patients with hepatocellular carcinoma (HCC) undergoing proton beam therapy (PBT). The purpose of this study is to identify the predictors for ULV preservation and quantify the capacity of proton beams in normal liver sparing during PBT. We reviewed planning data of 92 patients with single intrahepatic HCC tumors undergoing PBT. The potential clinical and planning factors that may affect ULV preservation were involved in multiple linear regression for ULV preservation rate. The significant factors were determined to be predictors and their influences were quantified. The median ULV preservation rate was 62.08%. All the assessed clinical factors showed significant effects on ULV preservation rate: clinical target volume (CTV), P  < 0.001; portal vein tumor thrombosis (PVTT), P  = 0.010; left lobe tumor, P  = 0.010. In contrast, none of the planning factors demonstrated significance. The coefficients of significant factors in multiple linear regression were 60.85 for intercept, −0.02 for CTV, −9.01 for PVTT and 8.31 for left lobe tumors. The capacity of proton beams to spare normal liver tissue during PBT for HCC is mainly affected by clinical factors. The baseline of the ULV preservation rate is 60.85%, decreasing 0.02% with each milliliter of CTV increase and 9.01% for tumors with PVTT, and increasing 8.31% for tumors limited to the left lobe. Further clinical studies should be carried out to correlate our dosimetric findings with clinical outcomes.